AN EXPERIMENTAL APPROACH TO CHANGING TAXPAYERSâ POSTURE MOTIVATION TOWARDS COMPLIANCE VIA MICROSITE - Sari, Elen Puspita; Susilowati, Yeye; Meiranto, Wahyu (Proceeding Fakultas Ekonomi, 2017)
This research describes an experiment designed to improve taxpayersâ posture motivation of the tax compliance decisions. Microsite from official website of edukasi.pajak.go.id as a public service announcement was shown to the participants. Pre and post experimental questionnaires were administered to measure differences in within group posture motivation about tax compliance. The results indicate that micro site were effective in improving viewers posture motivation towards tax compliance.Â  Â Keywords: posture motivation, tax compliance, micro site, experimentÂ